Tuning the Electronic Properties of Prussian Blue Analogues for Efficient Water Oxidation Electrocatalysis: Experimental and Computational Studies. Issue 19 (4th January 2018) - Alsaç, Elif Pınar; Ülker, Emine; Nune, Satya Vijaya Kumar; Dede, Yavuz; Karadas, Ferdi
Abstract: Although several Prussian Blue analogues (PBAs) have been investigated as water oxidation catalysts, the field lacks a comprehensive study that focuses on the design of the ideal PBA for this purpose. Here, members of a series of PBAs with different cyanide precursors have been investigated to study the effect of hexacyanometal groups on their electrocatalytic water oxidation activities. Cyclic voltammetric, chronoamperometric, and chronopotentiometric measurements have revealed a close relationship between the electron density of electroactive cobalt sites and electrocatalytic activity, which has also been confirmed by infrared and XPS studies. Furthermore, pH‐dependent cyclic voltammetry and computational studies have been performed to gain insight into the catalytic mechanism and electronic structure of cyanide‐based systems to identify possible intermediates and to assign the rate‐determining step of the target process. Abstract : Stable Prussian Blue‐type electrocatalysts : The effects of electroinactive hexacyanometal groups on the electroactive Co II site in Prussian Blue analogues have been probed by experimental and computational studies (see graphic).